Exploring entrepreneurial intentions and motivations: a comparative analysis of opportunity-driven and necessity-driven entrepreneurs - Batz Liñeiro, Aglaya; Romero Ochoa, Jhon Alexander; Montes de la Barrera, Jose (Journal of Innovation and Entrepreneurship, 2024)
This study investigates the impact of entrepreneurial attitudes, subjective norms, and perceived behavioral controls on entrepreneurial intention among two distinct groups of entrepreneurs: opportunity-driven and necessity-driven. It also explores the relationship between entrepreneurial motivations, intentions, and the number of ventures undertaken by entrepreneurs. Structural equation modeling and survey data from 201 necessity-driven entrepreneurs and 204 opportunity-driven entrepreneurs were utilized. Drawing on the Theory of Planned Behavior, the findings indicate that attitudes do not positively correlate with entrepreneurial intention for both types of entrepreneurs. Subjective norms significantly influence entrepreneurial intention among entrepreneurs by necessity but not among entrepreneurs by opportunity. Perceived behavioral controls exhibit a partial correlation with entrepreneurial intention, which is not significant for entrepreneurs by opportunity. Both motivations and entrepreneurial intention positively relate to the number of ventures undertaken by entrepreneurs by necessity, whereas motivations alone determine venture creation among entrepreneurs by opportunity. Furthermore, a significant correlation exists between being a female entrepreneur by necessity and entrepreneurial intention, while this relationship is not significant for women entrepreneurs by opportunity. These insights contribute to the literature on entrepreneurial intention and carry important policy and managerial implications in developing countries.